Comparing Health Information Channels between Male and Female Users of Iranian Public Libraries - Joulahi - Saravi, Laleh; Babalhavaeji, Fahimeh; Hariri, Nadjla (Archives of Advances in Biosciences, 2016)
Nowadays people are seeking health information to raise their awareness. They use many ways to get this information. This study examines the health information channels used by users of public libraries. The population of the present survey consisted of 461 users of public libraries throughout the country, randomly selected in a two-stage cluster sampling method. The questionnaire data were analyzed using SPSS. Cronbach’s alpha value was obtained as 0.89. Friedman test showed that there is a significant difference between the preferred channels of women and men for getting health information. Most health information was obtained through TV and the Internet channels. Most of the health knowledge was gained by users through parents, family members and self-study. Libraries played a second role after parents, schools, experiences of visiting doctors and self-study. Users preferred printed materials in the libraries to get health information. Television and the Internet were the most-used information channels. The public library as one of the channels of getting health information can provide reliable updated information to the users. Strengthening the print resources in the health field and introducing and evaluating scientific updated databases must be performed.